Confronting Climate Change Challenges to Dryland Cereal Production: A Call for Collaborative, Transdisciplinary Research, and Producer Engagement - Eigenbrode, Sanford D.; Binns, W. Patrick; Huggins, David R. (Frontiers in Ecology and Evolution, 2018)
Semi-arid cereal systems face challenges worldwide that are driven by ongoing and projected climate change. These challenges include ensuring cropping system resilience and productivity under changing water and temperature regimes while reversing soil degradation, reducing crop susceptibility to pests, pathogens and weed competition, and exploiting genetic resources to develop cultivars with resilience to climate stresses and improved compatibility with cropping system innovations. Meeting these interdependent challenges requires transdisciplinary efforts that integrate knowledge across many scientific domains. The USDA-NIFA-funded coordinated agricultural project, “Regional Approaches to Climate Change for Pacific Northwest Agriculture” (REACCH), employed this transdisciplinary approach to address climate change and sustainability challenges for rain-fed cereal-based systems in the semi-arid intermountain Pacific Northwest. To engage with and contribute to similar efforts globally, REACCH sponsored a workshop “Transitioning Cereal Systems to Adapt to Climate Change” (TCSACC) in November 2015. Participants from 17 countries and five continents with expertise in agronomy, crop physiology, crop modeling, crop protection, breeding and genetics, sociology and economics shared their perspectives, successes, and challenges to achieving transdisciplinary research integration for semi-arid cereal systems under changing climates. Conference goals were to: (1) strengthen the global network of researchers addressing climate change effects on semi-arid cereal-based systems, (2) share the approaches to achieving transdisciplinary collaboration to advance climate change resilience in cereal systems, and (3) identify the elements of a collaborative research agenda that are needed to advance global food security in the 21st century. This paper distills the conference themes and summarizes the calls to action that were discussed.